2012
DOI: 10.1093/mnras/sts112
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing foundations of a cosmic cathedral: searching the stars for M33's halo

Abstract: We use data from the Pan-Andromeda Archaeological Survey (PAndAS) to search for evidence of an extended halo component belonging to M33 (the Triangulum Galaxy). We identify a population of red giant branch (RGB) stars at large radii from M33's disk whose connection to the recently discovered extended "disk substructure" is ambiguous, and which may represent a "bona-fide" halo component. After first correcting for contamination from the Milky Way foreground population and misidentified background galaxies, we a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 141 publications
(178 reference statements)
1
14
0
Order By: Relevance
“…A previous contribution (Cockcroft et al 2013), based also on PAndAS data, detected the halo of M33 (a satellite of M31) out to very large radii, revealing hints of asymmetric morphology. Recent spectroscopic studies have shown evidence of a metalpoor halo in M31 (Chapman et al 2006;Kalirai et al 2006;Koch et al 2008), which had been largely missed in earlier work due to the presence of substantial contamination from the so-called southern Giant Stellar Stream (Ibata et al 2001), which pollutes almost all the inner halo region.…”
Section: Introductionmentioning
confidence: 82%
“…A previous contribution (Cockcroft et al 2013), based also on PAndAS data, detected the halo of M33 (a satellite of M31) out to very large radii, revealing hints of asymmetric morphology. Recent spectroscopic studies have shown evidence of a metalpoor halo in M31 (Chapman et al 2006;Kalirai et al 2006;Koch et al 2008), which had been largely missed in earlier work due to the presence of substantial contamination from the so-called southern Giant Stellar Stream (Ibata et al 2001), which pollutes almost all the inner halo region.…”
Section: Introductionmentioning
confidence: 82%
“…We also note that satellites of M33 as faint as those recently discovered around the LMC are sufficiently faint that they would be extremely challenging to detect in PAndAS imaging. Chapman et al (2013) the absence of a spatially extended population of globular clusters around M33 (Cockcroft et al 2011), as well as an absence of any obvious M33 stellar halo component (Cockcroft et al 2013;McMonigal et al 2016). It also means that it is possible that some of the globular clusters and dwarf galaxies currently associated with M31 were in fact originally associated with M33.…”
Section: Substructure In the Dwarf Galaxy Populationmentioning
confidence: 99%
“…The particular structure (star streams) seen in M33 could be associated with this history of mergers and interactions. In fact, many of the structures presented in McConnachie et al (2009McConnachie et al ( , 2010; Cockcroft et al (2013) and Wolfe et al (2013) around M31 and M33 can only be explained by these interactions. Deep Hα observations of M33 reveal the presence of low density Hii regions outside the optical disk (Hoopes et al 2001).…”
Section: Introductionmentioning
confidence: 99%